LABORATORY TESTING OF PITCHING CONVERTER WAVE ENERGY DEVICE - Ahadi Rahman (15511075), Arief
A Pitching Converter Wave Energy Device moves in a pitching manner as a response to the water waves on it to generate electricity. On this laboratory testing, 135 tests is underwent using a cylindrical physical model with 1:10 scale in Water Wave Laboratory of ITB. The model uses several ballasts configuration on the top side and one inside its bottom part to present some variations on its natural frequency. The tests are done in 3 differents depth which are 70 cm, 80 cm, and 90 cm with differents paddle and RPM configurations to generate various wave characteristics such as wave height (H), wave period (T), and wave length (L). Before the main tests is conducted, the wavemaker has to be calibrated and the wave is separated in regards of incident wave and reflected wave using Suzuki-Goda method for each test. From all of the tests conducted, the data is analyzed and the model configuration of 1 ballast at a depth of 80 cm gives the best result.